If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10x + 9) = 3 Reorder the terms: (9 + 10x) = 3 Remove parenthesis around (9 + 10x) 9 + 10x = 3 Solving 9 + 10x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 10x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 10x = 3 + -9 10x = 3 + -9 Combine like terms: 3 + -9 = -6 10x = -6 Divide each side by '10'. x = -0.6 Simplifying x = -0.6
| 3*5*6=153072 | | 5x-7=7x+6 | | 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= | | 0=x^2-21x+24 | | 8-0.5(x+3)=0.25(x+-1) | | -(4-m)=10 | | 6=-4k+2 | | 20y+2=46 | | 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= | | x^7=65 | | 4.9x^2-20x=0 | | 8+(y+2)=4(y-3) | | x+(x*0.25)=500000 | | 3n+4-4=n+20 | | 4t^2-9s^2=0 | | lnx^2-6lnx+5=0 | | (5x-2)-(3x-1)=(4x+3)-(5x-2) |